Advances and Clinical Perspectives in Bariatric and Metabolic Surgery - P.H. Najafguliyeva (Caucasian Medical Journal, 2026)
The aim of the study: Obesity and metabolic disorders remain among the most challenging health problems of the modern era, significantly affecting both quality of life and overall survival. The present study aimed to investigate the clinical efficacy of bariatric and metabolic surgery in the management of morbid obesity and associated metabolic disturbances, as well as to evaluate contemporary surgical approaches and long-term clinical outcomes.Materials and methods: A total of 68 patients underwent bariatric surgical procedures at the Department of Surgical Diseases of Azerbaijan Medical University between 2013 and 2024. The study population included 12 men and 56 women aged between 23 and 64 years. Type 2 diabetes mellitus and impaired glucose tolerance were diagnosed in 24 individuals, while dyslipidemia characterized by elevated cholesterol and triglyceride levels was detected in 39 patients. Sleep apnea syndrome was identified in 28 patients, all with body weights exceeding 100 kg. Arterial hypertension was present in 34 cases. Body mass index ranged from 35.3 kg/m² to 65.7 kg/m². Patient body weight varied between 94 kg and 193 kg, with heights ranging from 146 cm to 179 cm. Hyperinsulinemia was observed in 25 patients. Among female patients, reproductive and hormonal disorders were highly prevalent, including menstrual irregularities, ovarian dysfunction, endocrine imbalance, and infertility lasting longer than one year in several cases.Results and discussion: Postoperative follow-up periods ranged from 1 to 20 months. During the first six postoperative months, excess body weight loss reached 50–70%, while total body weight reduction ranged from 25% to 48%. Resolution of sleep apnea was observed in 27 patients. Blood glucose levels normalized in 19 patients, demonstrating the significant metabolic impact of surgical intervention. Lipid metabolism also improved considerably, with normalization of cholesterol levels in 26 patients and triglyceride levels in 32 patients. Insulin concentrations returned to normal values within the first two months in 5 patients and within six months in 20 patients. Restoration of regular menstrual cycles was noted in 34 female patients, indicating positive endocrine and reproductive outcomes after weight reduction surgery.Conclusion: Bariatric and metabolic surgery, as one of the most important achievements of modern medicine, is considered the gold standard in the treatment of obesity and its complications. This method provides not only a reduction in body mass, but also the restoration of metabolic homeostasis, an improvement in the quality of life and a significant reduction in mortality.